Autofiction as a Pillar of Juan Pablo Villalobos’ Literary Posture - Argüelles Rozada, Esther (2024)
The novels of Mexican writer Juan Pablo Villalobos have been recurrently linked to autofiction. As part of this narrative, No voy a pedirle a nadie que me crea (2016), Peluquería y letras (2022), and El pasado anda atrás de nosotros (2024) fall within this category. The connection of these works with autofiction is not solely the result of a strictly literary analysis but stems from a persistent association found in various paratexts, the writer's public statements, and diverse references shared by third parties – editors, critics, journalists, interviewers, etc. Also noteworthy in this regard are the autofictional elements present in the film adaptation of the first of these novels, directed by Fernando Frías de la Parra (2023), as well as certain strategies for its promotion. The focus of this work is to explore the importance of autofiction in the construction of a stable and defining literary posture (Meizoz, 2014).